Improvement of measles immunity among migrant populations: lessons learned from a prevalence study in a Swiss prison (Swiss Medical Weekly, 2011)
BACKGROUND: Measles persists worldwide despite the implementation of general vaccination campaigns. The environmental and demographic characteristics in many prisons increase the risk of measles epidemics. A large proportion of inmates come from countries where immunisation coverage is low. We aimed to estimate the susceptibility to measles among prisoners in order to implement preventative measures. METHODS: Serology screening for measles was carried out among 116 inmates in Switzerland’s largest pre-trial prison. Socio-demographic characteristics were collected through a structured questionnaire. Risk factors for lack of measles immunity were examined. RESULTS: A total of 7 out of 116 (6%) inmates were not immune to measles. All 37 inmates from sub-Saharan Africa were immune. Considering only people native from regions other than sub-Saharan Africa, 7 of 40 inmates born after 1981 were susceptible (18.5%), whereas none of the 39 inmates born in 1981 or before were susceptible (p = 0.006). CONCLUSION: Susceptibility to measles was fairly low in this prison population composed mainly of migrants. Living in sub-Saharan Africa during childhood, and birth before 1982 were protective factors associated with the presence of immunity against measles. The heterogeneity of vaccination campaigns in the various regions of the world, particularly in terms of the timing of their introduction and scale of diffusion, explains epidemiological variability. Targeted vaccination in accordance to origin and age would offer excellent herd immunity and would substantially reduce risks of outbreaks as well as costs.